Nesting of electron and hole Fermi surfaces in nonsuperconducting BaFe 2P2 - Arnold, B; Kasahara, S; Coldea, A; Terashima, T; Matsuda, Y; Shibauchi, T; Carrington, A (2011)

(untitled)
We report detailed measurements of the de Haas-van Alphen (dHvA) effect in BaFe2P2, which is the end member of the superconducting series, BaFe2(As1-xPx)2. Using high-purity samples, we are able to observe dHvA oscillations from all the sheets of the Fermi surface and hence build up a detailed picture of its structure. The results show the existence of a highly warped section of hole surface, which may be the origin of the nodal superconducting gap structure in this series. Importantly, we find that even for this nonsuperconducting end member, one of the hole surfaces almost exactly nests with the inner electron surface. This suggests that improved geometric nesting does not drive the increase in pairing strength with decreasing x in this system. © 2011 American Physical Society.